The Poetics of Jacobean Drama - Freer, Coburn (Book collections on Project MUSE., 2019)
The Poetics of Jacobean Drama argues for a rediscovered approach to the study of Renaissance drama. Coburn Freer observes that most modern criticism of this drama treats the plays as if they were written in prose, thus overlooking whole areas of dramatic meaning that were understood in the past. Such an understanding, he asserts, was common among writers, actors, audiences, and readers of the Elizabethan and Jacobean eras, and a knowledge of it is essential to a full appreciation of the characterization and dramatic structures in these plays. Freer explores the evolution of the modern reluctance to approach Renaissance drama as one would dramatic poetry - from the standpoint of a listener. Blank verse, the author shows, provided Jacobean dramatists with a poetic form against which they could work the pressures of experience within their characters. The writers' ability to work with and against this form provided infinite resources for delineating character and creating significant coherences in the structure of a play. The book also offers insights into what the Renaissance writer, actor, and playgoer would have regarded as the domain of poetry in drama. Topics discussed include the conditions of stage performance and the style of acting, Elizabethan education, the rise of printed texts and collected editions, and the comments of Elizabethan audiences and readers. Freer's commentary and theoretical explanations suggest both why and how we should pay closer attention to the poetry of Renaissance drama.